Spatial distribution of genetically superficial formations associated with siliciclastic rocks - Plateau of Southern Espinhaço (MG) - Brazil - Simões, Patrícia Mara Lage; Valadão, Roberto Célio; Oliveira, Cristiane Valéria de; Oliveira, Fãbio Soares; Santos, Politácito (Sociedade & Natureza, 2016)
The study area which lies on the western edge of the Southern Highlands Ridge, are predominant in siliciclastic rocks that integrate different geological units, we observed two distinct types of distribution patterns of shallow, linear and zonal training. This work aims to analyze the spatial distribution of surface formations stretch from the Southern Espinhaço Plateau located in the upper reaches of the Rio Pardo Small (MG), discussing the role played by the organization in litoestrutural spatiality of this soil cover. To perform such an investigation of spatial distribution maps of surface formations, geological structure map, and topographical and geological profiles were produced. The superficial formations observed in the study area have a spatial distribution essentially driven by the characteristics of the lithological and structural framework of the region. The linear distribution is related to structural features, such as faults, thrust faults, alignments, anticlines and synclines. Already zonal formations are influenced by differences between the resistance of different rocks to weathering processes. The study of the characteristics of surface formations and their associations with lithostructural aspects are essential to understand the geomorphic setting of the upper reaches of the Rio Pardo Small.